Hydrogen Interaction with Deep Surface Modified Zr-1Nb Alloy by High Intensity Ti Ion Implantation; Metals; Vol. 8, iss. 12 - Kashkarov E. B. Egor Borisovich; Ryabchikov A. I. Aleksandr Ilyich; Kurochkin A. V. Aleksandr Viktorovich; Syrtanov M. S. Maksim Sergeevich; Shevelev A. E. Aleksey Eduardovich; Obrosov A. Aleksey; Weifs S. Sabine (2018, 2018)
Title screen